Religiosidade popular: as práticas do benzimento nas fendas da modernização - Dadalto, Steffany Gonçalves (Universidade Federal de São Carlos, 2023)
Benzection is a practice with records from the period of the High Middle Ages, which remains in action and modernizing over time. In Brazil, the trade begins in the colonial period, at a time when medicine was scarce and with few professionals. In this context, the blessing helps in the treatment and cure of various diseases that afflict the popular, remaining in action in the contemporary period, existing and resisting in several locations in Brazil. This work proposes to address the origin of religiosity in man’s life, to analyze how syncretism was formed in colonial Brazil, context and development of benzection, as well as its forms of manifestations through the centuries, in an example within cultural geography. Counting on bibliographical research, essential for the accomplishment of this study, constituted by authors as Laura de Mello e Souza, Mircea Eliade, Silvia Federici and others. From these authors, we seek to understand how the practice of benzedeiras was formed and its characteristics and adaptations, addressing reports of this formation and how they were seen by society. The general objective of the research is to understand the popular healers, considering the oral tradition and the rite in the process of social interaction, with the purpose of understanding the origin, formation and permanence of these practices that are linked to culture, religion and popular medicine, interpreting the established interpersonal relationships, which keep the tradition still current. The research allowed the analysis of the profile of benzedeiras and from it was constituted the corpus of this work.
Popular religiosity: the practices of blessing in the cracks of modernization
Keywords: Cultura popular; Modernização; Benzimento; Religiosidade; Popular Culture; Modernization; Blessing; Religiosity; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA